Consumer Protection and Grievance Redressal in India - Sapna Devi (MultiTech Publisher, 2024)
Consumer protection in India has evolved significantly with the establishment of various laws and regulatory bodies designed to safeguard consumer rights. Despite these efforts, issues related to consumer awareness and grievance redressal continue to persist. With increasing consumerism and market complexity, effective mechanisms for protecting consumer rights and addressing grievances are crucial for ensuring fair practices and consumer satisfaction.This study is based on secondary data sourced from government reports, academic research, and industry analyses. The data provides insights into the current state of consumer protection, the level of consumer awareness, and the effectiveness of grievance redressal mechanisms in India. By analyzing these sources, the study aims to evaluate the strengths and weaknesses of existing systems and identify areas for improvement.The findings indicate that while there have been improvements in consumer protection laws and grievance redressal mechanisms, significant challenges remain. Many consumers are still unaware of their rights and the available avenues for seeking redressal. The effectiveness of grievance redressal systems varies, with some regions experiencing delays and inefficiencies in addressing consumer complaints.The study concludes that enhancing consumer protection in India requires increased efforts to raise awareness about consumer rights and streamline grievance redressal processes. Recommendations include improving public education on consumer rights, simplifying complaint procedures, and strengthening regulatory oversight to ensure timely and effective resolution of grievances.